Perbuatan Melawan Hukum Materiil menurut Hakim Pengadilan Negeri Kepanjen - Arrozi, Fakhruddin (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This paper describes the material tort against the decision of Pengadilan Negeri (PN) of Kepanjen No. 91/Pid.B/2008 / PN.KPJ on a post-verdict corruption of Constitutional Court of RI. No.003/PUU-IV/2006 and then analyzes from the standpoint of positive law and criminal (jinayah) Jurisprudence. The study concludes that although a tort is legally no longer valid in law of Indonesia after the Constitutional Courts decision but in the case of corruption, Pengadilan Negeri of Kepanjen still applies the rule of the material tort. The existence of obscurity formula of tort is caused by the interpretation of the law and jurisprudence on tort material conducted by PN Kepanjen. The action of Pengadilan Negeri of Kepanjen in performing legal discovery and referring to jurisprudence, according to the criminal jurisprudence perspective, is true because Islam encourages its followers to do ijtihad when the rules are silent on the case submitted to the judge. If the judge cannot do ijtihad, he should refer to the previous jurisprudence. Keywords: Law, material, corruption, jurisprudence